2012
DOI: 10.1002/ajim.22007
|View full text |Cite
|
Sign up to set email alerts
|

Shift work and the incidence of injury among police officers

Abstract: Higher injury risk was associated with night shift work in police officers. Night shift combined with high work activity was strongly associated with injury risk. There was a significantly higher probability of not being injured on day compared to midnight or afternoon shifts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 27 publications
4
44
1
2
Order By: Relevance
“…Police officers (n=419) from a mid-sized urban police department in the U.S. were injured on the midnight shift 72% more often than in the day shift (Incident Rate Ratio = 1.72, 95% CI 1.26-2.36, p = 0.0007). High activity level combined with midnight shift doubled the risk of occupational injury for police officers (IRR = 2.31, 95% CI 1.46-3.65, p = 0.0003) [27]. A long-term injury (>89 days) for the same police officers occurred three times more often during night versus day shift (IRR = 3.12, 95% CI 1.35-7.21, p = 0.01) and two times more often in night shift versus afternoon shifts (IRR = 2.21, 95% CI 1.06-4.68, p = 0.04) [28].…”
Section: Shift Work As Risk Factormentioning
confidence: 98%
“…Police officers (n=419) from a mid-sized urban police department in the U.S. were injured on the midnight shift 72% more often than in the day shift (Incident Rate Ratio = 1.72, 95% CI 1.26-2.36, p = 0.0007). High activity level combined with midnight shift doubled the risk of occupational injury for police officers (IRR = 2.31, 95% CI 1.46-3.65, p = 0.0003) [27]. A long-term injury (>89 days) for the same police officers occurred three times more often during night versus day shift (IRR = 3.12, 95% CI 1.35-7.21, p = 0.01) and two times more often in night shift versus afternoon shifts (IRR = 2.21, 95% CI 1.06-4.68, p = 0.04) [28].…”
Section: Shift Work As Risk Factormentioning
confidence: 98%
“…In our previous work, we found that the incidence of injury was associated with night shift work among police officers (17). However, little is known about the length of time off due to injury and how this may vary across different shifts.…”
Section: Present Studymentioning
confidence: 99%
“…Полицијски посао је изузетно опасан, а ризик од незгода много већи него у другим занимањима (Violanti et al, 2012). Могућност да се незгода догоди током ноћне смjене је чак три пута већа него током јутарње смене (Folkard & Lombardi, 2006).…”
Section: преглед литературеunclassified
“…Веома битно да се пројектују адекватни смјенски системи, нарочито у области полиције, који ће смањити могућност појаве разних проблема са којима се суочавају запослени а који могу бити опасни не само за полицијце већ и за ширу јавност (Violanti, et al, 2012). Важан аспект креирања адекватног смјенског распореда у области полицијске управе је потреба да се обезбиједи 24-часовна покривеност у свим областима рада (Baulk et al, 2009).…”
Section: преглед литературеunclassified